The Effect of Cocoa Pod Fermentation on Nutrient Intake of Bligon Goats - Rumadi, Rumadi; Yakin, Engkus Ainul (Journal of Tropical Animal Science and Technology, 2025)
The study aims to determine the effect of cocoa pod fermentation on nutrient consumption in bligon goats. This study lasted for 2 months, in October-November 2024 and was conducted in Kuniran, Selorejo Village, Girimarto District, Wonogiri Regency, Central Java. This study used a completely randomized design (CRD) analysis of variance with 3 treatments and 3 replications. The materials used were fermented cocoa pods. Treatment P0 = 30% Elephant grass + 70% Concentrate + 0% Cocoa Pod Fermentation, P1 = 25% Elephant grass + 70% Concentrate + 5% Cocoa Pod Fermentation, P2 = 20% Elephant grass + 70% Concentrate + 10% Cocoa Pod Fermentation. Parameters observed were dry matter intake, organic matter intake, and crude protein intake. The results showed that dry matter intake P0 = 1002.59 g/day/head, P1 = 1011.70 g/head/day, P2 = 1032.58 g/head/day. Organic matter intake P0 = 628.07 g/head/day, P1 = 660.03 g/head/day, P2 = 671.23 g/head/day and crude protein intake P0 = 110.97 g/head/day, P1 = 114.97 g/head/day, P2 = 122.56 g/head/day. The conclusion of this study is that the giving cocoa pods fermentation up to 10% increase dry matter intake, organic matter intake, and crude protein intake.